Kepak Nilai Kesejarahan Bagi Generasi Milenial Melalui Media Sosial Guna Membangun Revolusi Mental Ditengah Pandemi Global - Sutrisno Mohammad; Asmun W Wantu; Mohamad E. S Wahyudi (Universitas Negeri Gorontalo, 2021)
This Study aims to determined the historical value for millennials through social media. This study uses historical resarch methods with several steps such as Heuristics, Criticism, Interpretation and Historiography. In this study, it countains historical value that must be understoot by the millennial generation at this time, especially with the efficiencyof using social media such as Instagram, Tiktok, Youtube, etc.